2023
DOI: 10.1186/s12891-023-06656-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the prevalence of neck and shoulder pain among high school students: a cross-sectional survey in China

Abstract: Background After the COVID-19 outbreak, many Chinese high school students have increased their dependence on electronic devices for studying and life, which may affect the incidence of neck and shoulder pain (NSP) in Chinese adolescents. Methods To evaluate the prevalence of NSP in high school students and its associated risk factors during COVID-19, a survey was conducted among 5,046 high school students in Shanghai, Qinghai, Henan and Macao durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The prevalence of CNSNP is increasing, especially among younger people, due to the fast-paced nature of modern society and changes in living and working conditions 5 . Some studies had shown that the incidence of chronic neck pain in college students is proportional to the prolonged use of electronic devices and the various poor postures, which may be related to excessive stretching of the muscles and ligaments of the back neck, resulting in exerting excessive pressure on the intervertebral discs and surrounding tissues and leading to neck pain 6 . Most patients with neck pain will experience recurrence within 1–5 years, and one of the important reasons is the change in posture control 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CNSNP is increasing, especially among younger people, due to the fast-paced nature of modern society and changes in living and working conditions 5 . Some studies had shown that the incidence of chronic neck pain in college students is proportional to the prolonged use of electronic devices and the various poor postures, which may be related to excessive stretching of the muscles and ligaments of the back neck, resulting in exerting excessive pressure on the intervertebral discs and surrounding tissues and leading to neck pain 6 . Most patients with neck pain will experience recurrence within 1–5 years, and one of the important reasons is the change in posture control 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has furnished evidence indicating that students who bear the burden of heavy backpacks often report various physical discomforts such as pain, inflammation, puffiness, tiredness, and discomfort in the upper or lower sections of the back, upper or lower trapezius muscles, shoulders, neck, or forearm regions (12,13) . This new ergonomic backpack with additional anterior straps can help stabilize the backpack, preventing it from swinging or pulling the wearer backward, which can reduce the risk of falls and injuries.…”
Section: Introductionmentioning
confidence: 99%